Virtual Co-Creation: A Guide to Conducting Online Co-Creation Workshops. (19th October 2021) - Benson, Tony; Pedersen, Susanne; Tsalis, George; Futtrup, Rebecca; Dean, Moira; Aschemann-Witzel, Jessica
COVID-19 has impacted research worldwide, with many researchers turning to online methods. While online and co-creation research methods are well established, there are no instructional articles or guides for researchers aiming to conduct online co-creation workshops. Such workshops can provide quality data and are increasingly used. This methods paper addresses this gap by outlining the steps involved in conducting online co-creation workshops. Using the TruSTFood sustainability food labelling study as an example, this paper provides instructions and considerations for researchers. It serves as a guide for those interested in or new to this area and can be used to transfer existing research online owing to social distancing and the pandemic or new research beyond.